Impact of additional intravenous methylprednisolone pulse therapy on the quality of life in patients with dysthyroid optic neuropathy - Pelewicz, Maryla; Rymuza, Joanna; Pelewicz, Katarzyna; Miśkiewicz, Piotr (Journal of Medical Science, 2021)
Introduction. Dysthyroid optic neuropathy (DON) is a severe complication of Graves’ orbitopathy (GO). Treatment of DON should involve immediate administration of intravenous methylprednisolone (ivMP) in very high doses. It is recommended to include additional 12 pulses of ivMP according to a weekly schedule as a further step of the treatment process. The purpose of this study was to evaluate the influence of a 12-week ivMP treatment on the quality of life (QoL) in DON patients.Material and Methods. A retrospective study was conducted on 6 patients (the tests involved 8 individual eyes) with DON and treated with ivMP in very high doses, followed by orbital decompression in one patient. All patients were qualified for additional treatment with ivMP in a 12-week protocol and completed the Polish version of the GOQoL questionnaire before and after the therapy. Visual acuity (VA) and diplopia were examined prior to the administration of ivMP pulses for DON, as well as before and after the additional ivMP treatment.Results. A minimal clinically important difference in QoL was observed in four patients at the end of the additional ivMP therapy. A significant increase in VA was observed following additional pulses of ivMP compared to the evaluation at the time of the DON diagnosis (p=0.04).Conclusions. Applying additional 12 pulses of ivMP following DON therapy may impact QoL. Performing QoL assessment throughout the entire therapy in patients with DON is particularly important in the clinical practice. Final evaluation of QoL should be performed after completing the entire therapeutic process, which involves surgical treatment to correct diplopia.